Socio-economic inequalities in adolescent mental health in the UK: Multiple socio-economic indicators and reporter effects - Matthew Hazell; Emma Thornton; Hassan Haghparast-Bidgoli; Praveetha Patalay (Elsevier, 2022)
There are socio-economic inequalities in the experience of mental ill-health. However, less is known about the extent of inequalities by different indicators of socio-economic position (SEP). This is relevant for insights into the mechanisms by which these inequalities arise. For young people's mental health there is an additional layer of complexity provided by the widespread use of proxy reporters. Using data from the UK Millennium Cohort Study (N ​= ​10,969), we investigated the extent to which five SEP indicators (parent education, household income, household wealth, parent occupational status, and relative neighbourhood deprivation) predict adolescent internalising mental health (at ages 14 and 17 years) and how this varies as a function of reporter. Both parent report and adolescent self-report were considered. Regression models demonstrated that whilst greater disadvantage in all five SEP indicators were associated with greater parent-reported adolescent mental health symptoms, only income, wealth, and occupational status were associated with self-reported mental health symptoms at ages 14 and 17 years. The magnitude of these effects was greater for parent-reported than self-reported adolescent internalising symptoms: SEP indicators jointly predicted 4.73% and 4.06% of the variance in parent-reported symptoms at ages 14 and 17 compared to 0.58% and 0.60% of the variance in self-reported internalising mental health. Household income predicted the most variance in parent reported adolescent internalising symptoms (2.95% variance at age 14 & 2.64% at age 17) and wealth the most for self-reported internalising symptoms (0.42% variance at age 14 & 0.36% at age 17). Interestingly, the gradient and variance explained of parent-reported adolescent mental health across SEP indicators mirrors that of parent's own mental health (for example, income explained 4.89% variance at the age 14 sweep). Our findings highlight that the relevance of different SEP indicators to adolescent internalising mental health differs between parent and adolescent reports. Therefore, it is important to consider the various perspectives of mental health inequalities gained from different types of reporters.